Molecular mechanism of glucocorticoid-induced hyperglycemia - Sari, Destika Ambar; Samodra, Galih; Kusuma, Ikhwan Yuda (Indonesian Young Scientist Group and UPN Veteran Jakarta, 2021)
Glucocorticoids are widely used as strong anti-inflammatory and immunosuppressive drugs to treat various diseases. However, the use of glucocorticoids can cause several side effects, such as hyperglycemia. This review aims to discuss the effect of glucocorticoids on increasing glucose in molecular levels based on literature studies. A literature searching was carried out on the PubMed, Science Direct, and Google Scholar databases published in 2010-2020. Glucocorticoids can cause an increase in blood glucose levels by several mechanisms. In the liver, glucocorticoids increase endogenous plasma glucose and stimulate gluconeogenesis. Glucocorticoids increase the production of non-esterified fatty acids which affect the signal transduction of insulin receptor substrate-1 in skeletal muscle. In adipose, glucocorticoids increase lipolysis and visceral adiposity through increased transcription and expression of protein adipose triglyceride lipase and hormone-sensitive lipase. In pancreatic beta cells, glucocorticoids directly inhibit the beta cell response to glucose through the role of protein kinase B and protein kinase C. At the molecular level, glucocorticoids can cause hyperglycemia through mechanisms in the liver, skeletal muscle tissue, adipose tissue, and pancreatic beta cells.